Dissolved organic matter mediates the interactions between bacterial community and heavy metal fractionation in contaminated coal mine soils - Wei Lin; Xiaolong Guo; Yili Wang; Junlin Zhao; Xiang Cheng; Yingjie Li; Chunyang Zhou (Ecotoxicology and Environmental Safety)
Heavy metal (HM) contamination in coal mine soils disrupts local bacterial networks, leading to prolonged soil deterioration. Dissolved organic matter (DOM), a crucial soil component, actively modulates both bacterial metabolism and HM mobilization. Despite its significance, our understanding of the complex interactions among bacterial communities, soil chemical and DOM properties, and HM fractionation remains limited. In this study, DOM and bacterial communities from three contaminated mines with varying HM levels and soil properties were analyzed using optical methods and high-throughput sequencing technique. Our results revealed pH and DOM composition, especially the ratio of recalcitrant to labile substances, as key environmental drivers of HM mobilization. Moreover, the composition of bacterial community, particularly the keystone and abundant species, exhibits pronounced site-specificity and HM-dependency. Distinct characteristic genera that are pertinent to HM tolerance/mobility were identified across three mines. Specifically, in Zibo (ZB) soils, Rhodococcus, Acinetobacter, and Pseudomonas significantly regulated the fractionation of Pb, Cu, Se, and Hg possibly via protein-like exudates releasing. In Zaozhuang (ZZ) soils, relationships were recognized between Reyranella, oxides associated Pb, and soil cation exchange capacity. Paenibacillus and Fictibacillus contributed to Se mobilization/tolerance in Linyi (LY) soils. Based on these field findings, two mechanisms were identified for how DOM mediates interactions between HM fractionation and bacterial communities. First, metal-resistant bacteria can produce labile DOM compounds, modifying HM fractionation and reducing metal bioavailability, as observed in ZB soils. Second, humic substances in DOM promoted the development of cohesive bacterial networks featuring metal-resistant keystone bacteria, thereby enhancing community resistance to metal contamination, as evidenced in LY and ZZ soils. Overall, this study provides field evidence elucidating the multilateral interactions among bacterial communities, soil chemical and DOM properties, and HM fractionation, underscoring the significant role of DOM in connecting soil bacterial activity and HM mobilization.